Influence of blood flow restriction training combined with resistance training on physical function of college football players - Chen, Yun (Quality in Sport, 2025)
Methods: A total of 48 male football players aged (20.67±1.34) years old were studied. The changes of lower limb muscle strength, longitudinal jump, fast sprint and isokinetic muscle strength before and after 8 weeks of training were compared. Results: 1) The peak torque of knee extension and flexion on both sides increased significantly in both groups (p < 0.01). The peak torque of knee flexion and extension in both sides of the experimental group was significantly better than that in the control group (p < 0.05). 2) the squat, CMJ and SJ test scores of the experimental group were better than those of the control group (P=0.036, 0.049, 0.016); 3) the direction changing ability and 30-meter sprint performance of the experimental group were significantly improved (P=0.006, 0.036), the 30-meter sprint ability of the control group was significantly improved (P=0.047), the direction changing ability and 30-meter sprint performance of the experimental group were significantly better than the control group (P=0.022, 0.028); 4) Serum nitric oxide and vascular endothelial growth factor in the experimental group were significantly increased compared with before the experiment (P=0.001, 0.000), endothelin was significantly decreased compared with before the experiment (P=0.000), and nitric oxide and vascular endothelial growth factor in the control group were significantly increased compared with before the experiment (P=0.027, 0.000). Endothelin had no significant change compared with before the experiment (P=0.068); After the experiment, nitric oxide and VEGF in the experimental group were significantly higher than those in the control group (P=0.032, 0.001), and endothelin was significantly lower than that in the control group (P=0.000).